'I have been dreaming about Chinese becoming the number one language in the world': Chinese language educators' language ideologies in Myanmar. Issue 1 (2nd January 2023) - Lou, Kaiyang; Xiong, Tao; Peng, Yue
ABSTRACT: Along with China's economic development and expanding cultural influence, the Chinese language has attracted an increasing number of learners in Myanmar, a culturally and linguistically diverse country. However, little is known about local Chinese teachers' language ideologies toward the Chinese language and Chinese language education against the societal, economic, and cultural backdrop in and beyond Myanmar, which constitutes what this study is intended to investigate. Data were collected from semi-structured interviews with 12 Chinese educators in Myanmar, followed by an inductive analysis process. Three themes were identified representing the educators' positive attitude toward viewing Chinese and Chinese language education as a resource for claiming cultural identity, accessing social capital, and enhancing regional relationships and development. The study yields implications relating to Myanmar's language and language education policy, the expansion of Chinese language education, and Chinese language educators' professional development.